2022
DOI: 10.3389/fmolb.2021.797689
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lncRNAs NEAT1 and lnc-DC in Serum From Patients With Behçet’s Disease Can Be Used as Predictors of Disease

Abstract: Background: Behçet’s disease (BD) is a chronic autoimmune disease. The early diagnosis of BD is very important to avoid serious and/or fatal complications such as eye damage, severe neurological involvement, and large vessel occlusion. New, sensitive biomarkers would aid in rapid diagnosis, the monitoring of disease activity, and the response to treatment.Methods: This study’s aim is to identify two immune system-related BD biomarkers. We measured long non-coding RNAs (lncRNAs) NEAT1 (nuclear-enriched abundant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
1
2
1
Order By: Relevance
“…NEAT1 may be used to monitor and control subclinical inflammatory reactions of BD, thus, preventing the diseases progression and development. On the other hand, our results may disagree with the outcome of the study by Mohammed and coworkers ( Mohammed et al, 2021 ). This could be attributed to the difference in the applied therapeutic options as well as disease state, patient’s symptoms, and subgroups.…”
Section: Discussioncontrasting
confidence: 99%
“…NEAT1 may be used to monitor and control subclinical inflammatory reactions of BD, thus, preventing the diseases progression and development. On the other hand, our results may disagree with the outcome of the study by Mohammed and coworkers ( Mohammed et al, 2021 ). This could be attributed to the difference in the applied therapeutic options as well as disease state, patient’s symptoms, and subgroups.…”
Section: Discussioncontrasting
confidence: 99%
“…To the best of our knowledge, no previous studies illustrated the role of NEAT-1 in vitiligo patients. However, studies agreed with our results that the expression of NEAT-1 tends to increase in autoimmune diseases such as RA, SLE, multiple sclerosis and Behçet's disease which are autoimmune diseases like vitiligo [7,8,19,20].…”
Section: Discussionsupporting
confidence: 92%
“…It has previously been shown that lncRNAs were expressed in serum ( Mohammed et al, 2022 )– ( Visconti et al, 2020 ). The RT2 SYBR Green PCR kit (Qiagen, Maryland, USA) was used to evaluate the expression of the lncRNAs IFNG-AS1 and GAS5 in serum using specific primers supplied by Qiagen, (Valencia, CA, USA); for IFNG-AS1 (Catalog no; 330701LPH20079A, Accession no, ENST00000536914.0) and GAS5 (Catalog no; 330701LPH11340A, Accession no, NR_002578.2) and we used GAPDH primer (Catalog no: 330701 LPH31725A, Accession no: ENST00000496049.0) to standardize the expression pattern and quantify the target long non-coding RNAs ( Li et al, 2016 ), ( Peng et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%